Perjuangan Kesetaraan Gender Tokoh Wanita Dan Nilai Pendidikan Dalam Novel Gadis Kretek Karya Ratih Kumala - Maftuhah; journal journal (Jurnal Pendidikan Islam, 2019)
Abstract: This study aims to describe and explain: (1) the struggle forgender equality of female characters in Ratih Kumala's novel KretekGirl, and (2) educational values in Ratih Kumala's novel Kretek Girl.This type of research is qualitative research. This study used descriptivequalitative method. Qualitative descriptive method is a researchprocedure that produces description data in the form of words. Theresearch data is a novel by Kretek Girl by Ratih Kumala.This study usesa feminism approach to describe the profile of female characters, thestruggle for gender equality, and the sociological approach of literatureto find out about the social conditions of the community in RatihKumala's novel Kretek Girl. The data collection technique used in thisstudy was to read the entire contents of the novel and document analysis.The results of this study are as follows: (1) The struggle for genderequality of female leaders in Ratih Kumala's novel Kretek Gadis isagainst forms of gender injustice in the form of (a) stereotypes, (b)marginalization of women, (c) subordination of work, and (d) internalviolence household. (2) Ratih Kumala's novel Kretek Girls educationalvalues include: (a) the value of religious education that emphasizesbetween humans and God, (b) the value of social education refers to therelationship of individuals to other individuals in a society (c) the valueof education morals that relate to the good or bad of human behavior,and (d) the value of cultural / customary education that is related totradition, people's habits.